PENGARUH INFLASI, KEBIJAKAN FISKAL DAN MONETER TERHADAP PENGANGGURAN DI INDONESIA - asyulinda, Asyulinda; Amar, Syamsul; Aimon, Hasdi (Program Studi Magister Ilmu Ekonomi, 2015)
This study aims to analyze(1)The effect ofgoverment expenditure on inflaton,(2)The effect of tax on inflaton (3)The effect ofthe money supply on inflaton (4)The effect ofinterest rates on inflaton and (5) The effect ofinflation,government expenditure, tax, the money supply, interest rates on the labor force in the Indonesia state. Data used time series of 1980 - 2013. This article use analyzer model path analysis. The result of research concludesthat (1)the incomehave a significantand positive impact onthe investment,interest rateshave significantand negatively impact onthe investment,government expenditure significantlyandpositiveon the investment, while inflationis notsignificant and negativeeffecton the investmentinNorth Sumatera.If incomeincreases, the investmentwill also increase. If interest rates increases, the investment will decreases, and If government expenditure increases, the investment will increases. (2)the investmenthave a significantand positive impact onthe income, government expenditure is not significant and positive on the income,the money supplyhave significantand positive impact onthe income, and tax have significantand negatively impact onthe income in North Sumatera. If investmentincreases, the incomewill also increase,if the money supply increase, the income will increase, and then if the tax increase, the income will decreases. Keywords :interest rates, goverment expenditure, inflation, the money supply, tax and labor force.